Regulation of Antimycin Biosynthesis Is Controlled by the ClpXP Protease - Bohdan Bilyk (American Society for Microbiology, 2020)
ABSTRACT The survival of any microbe relies on its ability to respond to environmental change. Use of extracytoplasmic function (ECF) RNA polymerase sigma (σ) factors is a major strategy enabling dynamic responses to extracellular signals. Streptomyces species harbor a large number of ECF σ factors, nearly all of which are uncharacterized, but those that have been characterized generally regulate genes required for morphological differentiation and/or response to environmental stress, except for σAntA, which regulates starter-unit biosynthesis in the production of antimycin, an anticancer compound. Unlike a canonical ECF σ factor, whose activity is regulated by a cognate anti-σ factor, σAntA is an orphan, raising intriguing questions about how its activity may be controlled. Here, we reconstituted in vitro ClpXP proteolysis of σAntA but not of a variant lacking a C-terminal di-alanine motif. Furthermore, we show that the abundance of σAntA in vivo was enhanced by removal of the ClpXP recognition sequence and that levels of the protein rose when cellular ClpXP protease activity was abolished. These data establish direct proteolysis as an alternative and, thus far, unique control strategy for an ECF RNA polymerase σ factor and expands the paradigmatic understanding of microbial signal transduction regulation. IMPORTANCE Natural products produced by Streptomyces species underpin many industrially and medically important compounds. However, the majority of the ∼30 biosynthetic pathways harbored by an average species are not expressed in the laboratory. This unrevealed biochemical diversity is believed to comprise an untapped resource for natural product drug discovery. Major roadblocks preventing the exploitation of unexpressed biosynthetic pathways are a lack of insight into their regulation and limited technology for activating their expression. Our findings reveal that the abundance of σAntA, which is the cluster-situated regulator of antimycin biosynthesis, is controlled by the ClpXP protease. These data link proteolysis to the regulation of natural product biosynthesis for the first time to our knowledge, and we anticipate that this will emerge as a major strategy by which actinobacteria regulate production of their natural products. Further study of this process will advance understanding of how expression of secondary metabolism is controlled and will aid pursuit of activating unexpressed biosynthetic pathways.